Identification of microRNAs as potential cellular monocytic biomarkers in the early phase of myocardial infarction: a pilot study. Issue 1 (December 2017) - Parahuleva, Mariana; Euler, Gerhild; Mardini, Amar; Parviz, Behnoush; Schieffer, Bernhard; Schulz, Rainer; Aslam, Muhammad
Abstract MicroRNA has been increasingly suggested to be involved in vascular inflammation. The aim of this study was to assess the expression profile of miRs as possible novel cellular biomarkers in circulating monocytes in patients with ST-segment elevation myocardial infarction (STEMI). Microarray techniques and TaqMan polymerase chain reaction were used to analyse the global expression of 352 miRNAs in peripheral blood monocytes from healthy donors (n = 20) and patients (n = 24) with acute STEMI. The expression level of miR-143 in monocytes from STEMI patients compared to healthy controls was increased, whereas the expression of miR-1, -92a, -99a, and -223 was reduced significantly. During 3.5 ± 1.5 months of follow-up miR-1 and -223 were back to baseline, whereas miR-92a and -99a return to normal levels over 3 months, but remained lower than healthy controls. Furthermore, monocytic expression of miR-143 was positively correlated with hs-CRP (R2  = 0.338; P < 0.031), but not with cTnT. Importantly, treatment of monocytes isolated from healthy individuals with INFγ, but not LPS or TNFα caused an upregulation of miR-143 and downregulation of miR-1. Our findings identify circulating monocytes as putative biomarkers and as novel carriers for the cell-specific transfer of miRs in the early phase of myocardial infarction.